Post-colonial urban shapes and challenges: reading tradition in north-western Africa - Correia, Jorge (2018)
North-western Africa’s history gathers a palimpsest of powers and regimes where European colonialism has played a significant role in city shaping. An attentive reading suggests tradition has been both a conspicuous and a neglected instrument for post-colonial urban challenges. Evidence of Portuguese and Spanish military architecture along coastal towns showcases a scenario of isolated enclaves as early as the 15th century. With the exception of Ceuta and Melilla, all strongholds were lost to the royal Moroccan dynasties in the following centuries. Later, during the first half of the 1900s, Spaniards and French divided the kingdom into areas of Protectorate, respectively in the north and the central south. Acting as de facto colonial powers, their action on cities was never to touch the historical centres - medina - but rather build their modern villes nouvelles on adjacent grounds. This division marked a clear prejudiced clash between sectors favouring the settlement of European residents and others for native population. Such policy ended up having an important and non-deliberate side effect on the freezing of the traditional built environment of the medina’s quarters, despite preventing it from fostering preservationist efforts to fight increasing insalubrity problems. Furthermore, colonialism neglected a deeper research on traditional ways of living and building, thus leaving no fertile terrain for post-colonial urban renewals and expansions that instead have been copying Western models of mass housing to shelter the fast growing Moroccan population. Everyday social practices, expressed in codes of privacy and neighbourhood relationships and structured around courtyard houses, accessed by a hierarchy of thoroughfare streets leading to dead-end lanes, have been substituted by heavily pierced block façades. The response lacked an attention to social needs still indexed to Islam and only perceived progress as an acritical copy of pre-independence models. The Spanish enclave of Ceuta portrays a different path. For centuries an important Muslim commercial stronghold, the city was conquered by the Portuguese in 1415 and stayed in European hands ever since. The arrival of a new power and creed sought the foundation of a new Christian image. These early modern decisions still resonate in the city’s centre current urban morphology and were further developed by Spain who has taken over since 1640. Indeed, an intentional legitimation of Iberian heritage, favouring a neo-Baroque skyline to the city rather than assuming it in continuity with the Islamic one, clearly shows how policies of Europeanisation have challenged conceptions of identity in a disputed border territory. This paper wishes to explore the colonial sphere of urbanization in North-western Africa and its bias legacy to contemporaneity. In fact, a post-colonial analysis reveals, on the one hand, the resilience of colonialism in the production of residential spaces, noticeably contrary to traditional standards still valid in Morocco. On the other hand, the impact of an institutional policy of heritage manipulation has masked a past in Ceuta that only recently has been rediscovered. Either way, cultural clashes appear to support regimes rather than understanding people practices or the natural historical shaping of a city.